Rheological analysis of saliva samples in the context of phonation in ectodermal dysplasia - Eckhardt, Maximilian; Tur, Bogac; Heinrich, Anna; Wolfsteiner, Sophie; Schlicht, Samuel; Drummer, Dietmar; Wendler, Olaf; Schneider, Holm; Semmler, Marion (Applied Rheology, 2025)
Ectodermal dysplasia (ED) is a rare inherited disorder affecting embryonic ectoderm structures, leading to reduced development of skin appendages and certain eccrine glands. Displaying reduced salivation and impaired acoustic quality in males, ED offers a unique chance to study the role of laryngeal mucus in the phonation process. This study analyzed saliva rheology as a non-invasive substitute for laryngeal mucus to investigate potential causal relationships. Saliva samples from 36 ED patients and 99 controls were collected for 5 min following a 15 min abstention from eating, drinking, or smoking. The viscoelastic properties have been measured by a rheometer with a parallel plate system. Storage (G′) and loss (G″) moduli were recorded and compared between ED and controls. ED subjects exhibited significantly lower G′ and G″ at lower frequencies and strains, yet slightly higher values at increased frequencies and strains among males. These findings suggest reduced resistance of saliva to external forces for ED. Transferred to the laryngeal level, this behavior might impair the mucus’ retention rate on the vocal folds. The results also hint at altered hyaluronic acid content in ED, guiding further correlation studies investigating voice conspicuitie
Keywords: ectodermal dysplasia; rheology; phonation; vocal folds